BENGKEL MODIFIKASI DAN PENJUALAN MOTOR BEKAS KOTA BANJARBARU - Rozy, Muhammad Ridho Alfa; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
The high number of motorbike users in Indonesia means that the market demand for new motorbikes is also increasing every year. and this will definitely have a bad impact in the future where there will definitely be a buildup of scrap from used motorbikes that have not been properly processed, this is what makes some people create motorbike modification facilities. However, the problem in the field is the lack of integrated modification facilities and rarely having interesting 3R activity platforms, especially in Banjarbaru. So, to answer this problem, a Banjarbaru City Used Motorcycle Modification and Sales Workshop was designed using the superimposition design method to optimize and make the 3R (Reduce, Reuse and Recycle) activities in it more attractive. which presents programs on repair, modification and sales of used motorbikes.